Patient Derived Xenografts Expand Human Primary Pancreatic Tumor Tissue Availability for ex vivo Irreversible Electroporation Testing - Brock, Rebecca M.; Beitel-White, Natalie; Coutermarsh-Ott, Sheryl; Grider, Douglas J.; Lorenzo, Melvin F.; Ringel-Scaia, Veronica M.; Manuchehrabadi, Navid; Martin, Robert C. G.; Davalos, Rafael V.; Allen, Irving C. (Frontiers in Oncology, 2020)
New methods of tumor ablation have shown exciting efficacy in pre-clinical models but often demonstrate limited success in the clinic. Due to a lack of quality or quantity in primary malignant tissue specimens, therapeutic development and optimization studies are typically conducted on healthy tissue or cell-line derived rodent tumors that don’t allow for high resolution modeling of mechanical, chemical, and biological properties. These surrogates do not accurately recapitulate many critical components of the tumor microenvironment that can impact in situ treatment success. Here, we propose utilizing patient-derived xenograft (PDX) models to propagate clinically relevant tumor specimens for the optimization and development of novel tumor ablation modalities. Specimens from three individual pancreatic ductal adenocarcinoma (PDAC) patients were utilized to generate PDX models. This process generated 15-18 tumors that were allowed to expand to 1.5 cm in diameter over the course of 50-70 days. The PDX tumors were morphologically and pathologically identical to primary tumor tissue. Likewise, the PDX tumors were also found to be physiologically superior to other in vitro and ex vivo models based on immortalized cell lines. We utilized the PDX tumors to refine and optimize irreversible electroporation (IRE) treatment parameters. IRE, a novel, non-thermal tumor ablation modality, is being evaluated in a diverse range of cancer clinical trials including pancreatic cancer. The PDX tumors were compared against either Pan02 mouse derived tumors or resected tissue from human PDAC patients. The PDX tumors demonstrated similar changes in electrical conductivity and Joule heating following IRE treatment. Computational modeling revealed a high similarity in the predicted ablation size of the PDX tumors that closely correlate with the data generated with the primary human pancreatic tumor tissue. Gene expression analysis revealed that IRE treatment resulted in an increase in biological pathway signaling associated with interferon gamma signaling, necrosis and mitochondria dysfunction, suggesting potential co-therapy targets. Together, these findings highlight the utility of the PDX system in tumor ablation modeling for IRE and increasing clinical application efficacy. It is also feasible that the use of PDX models will significantly benefit other ablation modality testing beyond IRE.